EU policy towards Central and Eastern Europe: Development of pre-accession strategies - Vilpišauskas, Ramūnas (Politologija, 1997)
The author continues the analysis started in the previous issue. The same analytical framework is used to discuss European Union's (EU's) policy towards the Central and Eastern European countries (CEECs) and its dynamics after the Copenhagen summit. The policy development was brought into a new stage during this period, and its main outcome was the pre-accession strategy designed for the CEECs that expressed the wish to become EU members. The main focus of the article is defining the main factors that seem to have influenced EU's policy and attempting to explain changes in the policy content. The Copenhagen Council decisions indicated the beginning of a long-term search for integration strategy on the part of EU decision-makers. This indicated that EU's policy towards CEECs started developing towards being outward-oriented and proactive rather than inward-oriented and reactive. This was reflected by the decisions of the Essen Council.The continuous pressure on the part of CEECs leaders resulting because of the mismatch between their expectations and actual EU's policy, critique of EU policy coming from the expert community, initiative showed by some Commissioners and member states, and two-level bargains were important factors that influenced changes in the policy nature and content. The significant result of the policy change was the White Book with a detailed list of measures to be implemented by CEECs seeking to join the EU. On the whole, the policy-making process was characterized by successive stages emerging as the outcome of partial bargains and compromises, reached under pressure of internal and external forces and commitments. The analysis illustrates that the negotiations process exposes a number of diverging interests and preferences coming from the different levels of governments, the Commission, and interest groups.Therefore, in order to understand better the outcome of policy-making, one needs to examine both the technocratic consensus emphasized by neofunctionalism, and the domestic coalition building that liberal intergovernmentalism focuses on. The EU policy towards CEECs progressed mainly as a result of changing policy preferences within the Commission and the member states. The position of the Commission, as I showed before, was not coherent and stable. Its negotiating position was influenced by its administrative capacity, the number of competing priorities, as well as the leadership of certain commissioners. The positions of member states were dependent on a number of factors including domestic opinion, electoral commitments, interest groups, leadership, geographical proximity, and security and commercial interest in Eastern Europe. Therefore, the cleavage was not simply between supporters and opponents of the EU integrationist policy as a whole but cut across the institutions and different policy areas.Thus, during the period under review, the policy-making process was characterized by a tension between the perceived necessity of integrative action towards CEECs based on broader political and economic objectives and internal inertia coming from the restrictive economic interests. The tension is resolved, and policy changes occur when there is a certain combination of internal forces and pressure from outside, which change the balance in the internal compromise by adding weight to the previous minority view in the internal debate.
Keywords: -